Peran Enterpreneur Oriantation dalam Mendorong Social Media Adoption dan Creativity Product untuk Meningkatkan Bisnis Performance - Nabhan, Faqih; Silfiyah, Luluk (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2024)
This research aims to determine the influence of entrepreneurial orientation on business performance mediated by social media adoption and product creativity. The research population was all culinary MSMEs in the city of Salatiga with a sample of 100 samples using the Lemeshow formula, purposive sampling method and data collection using a questionnaire. Data was processed using SmartPLS 4.0 software with a Partial Least Square approach. The findings of this research are: 1) There is a positive and significant influence between entrepreneurial orientation, business performance, social media adoption and product creativity. 2) social media adoption has a significant positive effect as a mediating variable, but product creativity has an insignificant positive effect as a mediating variable on the influence of entrepreneurial orientation on business performance. The contribution and new value of this research is that it provides a new perspective on the Service Dominant Logic theory and a further description of the role of entrepreneurial orientation on business performance. This shows that high levels of social media adoption and product creativity tend to increase entrepreneurial orientation and business performance.